Antioxidant Status of Sprague-Dawley Female Rat with Curcuminoids Nanoparticles of Balittro Curcuma - Laksmi Ambarsari; Riska Febrianti; Edy Djauhari Purwakusumah (IPB University, 2019)
Curcuma (Curcuma xanthorrhiza) is an Indonesian herbs plant with antioxidant activity. This research aimed to measure the increase of curcuminoids bioavailability through the effectivity of nanoparticle curcuminoids as an antioxidant for carbon tetrachloride (CCl4) induced rats. Nanoparticle curcuminoids were produced by homogenization-ultrasonication method showed results particle size of curcuminoids nanoparticle was 141.85±38.82 nm with polydispersity index was 0.233 and entrapment efficiency was 71%. During the treatment, the rat’s body weight was increased. Clinical symptoms of rats (behavior and feces) were normal. Nanoparticle curcuminoids can decrease malondialdehyde concentrations and increase peroxide, glutathione peroxide, and superoxide dismutase activity. Keywords : antioxidant, curcuminoid, solid lipid nanoparticle, Curcuma.